In utero smoke exposure and role of maternal and infant glutathione S-transferase genes on airway responsiveness and lung function in infancy - Murdzoska, J.; Devadason, S.; Khoo, S.; Landau, L.; Young, S.; Goldblatt, J.; Zhang, Guicheng; Le Souëf, P.; Hayden, C. (American Thoracic Society, 2010)
Rationale: Xenobiotics in the maternal circulation are capable of crossing the placental barrier so a reduction in the mother and fetus's detoxification ability due to genetic variation in the glutathione S-transferases (GSTs) could expose the fetus to higher levels of toxins. Objectives: To investigate the interactive effects of maternal smoking during pregnancy with maternal and infant GST genotypes on airway responsiveness (AR) and lung function in infancy. Methods: GSTT1, GSTP1 and GSTM1 were genotyped in infants and mothers, in utero smoke exposure was evaluated by questionnaire, AR was assessed by histamine challenge and V?maxFRC was measured using the rapid thoracoabdominal compression technique. We investigated the interactive effects of maternal smoking during pregnancy with maternal and infant GST genes on AR and lung function at 1, 6, and 12 months and longitudinally throughout the first year. Measurements and Main Results: Infant and/or maternal GSTT1 nonnull was associated with reduced AR at 12 months and throughout the first year and increased V?maxFRC at 6 months. Maternal GSTP1 Val/Val or Ile/Val was associated with increased V?maxFRC at 6 months. In infants exposed to in utero smoke, infant and/or maternal GSTT1 nonnull was associated with reduced AR at 1 month and throughout the first year and increased V?maxFRC throughout the first year. Maternal GSTP1 Val/Val or Ile/Val was associated with increased V?maxFRC at 6 months. Conclusions: GST genes may be especially important during fetal development as they may modify, through proficient detoxification, the effects of in utero maternal smoke exposure on AR and lung function in infants.